Acknowledging consumption : a review of new studies - Miller, Daniel, 1954- (Material cultures., 1995)
This work is a survey of the writings on consumption produced over the last decade. There are chapters on consumption studies in anthropology, consumer behaviour, economics, geography, history, media studies, psychology and sociology.